Seasonal changes in the histomorphological and spermatogenic activity controlled by proliferation and apoptosis of germ cells of the bull testis in a semiarid environment (Algeria) - Belkhiri, Y; Benbia, S (Journal of the Hellenic Veterinary Medical Society, 2025)
The present study was carried out to investigate the spermatogenic activity of mature bull local breed and effect of season’s changes on the testes activity and main histomorpholgical parameters. At the beginning of each season (autumn, winter, spring, summer), among the study group, nine (09) bulls were randomly selected, slaughtered and their left testes were processed by histological and histometric methods. Statistical analysis revealed that the total numbers of leydig, sertoli and germ cells per testis including primary and secondary spermatocytes, round and elongated spermtids were significantly higher during the breeding season (autumn). The diameter of the seminiferous tubules and the height of germinal epithelium demonstrated higher (p<0.05) significant in autumn and winter. The increase in spermatogenesis process lead to increase the diameter and height of seminiferous. However, the Length of seminiferous tubules did not change (P>0.05) due to season. A positive linear relationship (P<0.05) was found between Sertoli cell efficiency (Y) and the season (X), which was characterized by the equation Y= -1.322 x+7.481 and a coefficient of correlation (R) of 0.323. A significant positive correlation was seen between the total number of Sertoli cells and of spermatogonia (r = 0.998; P <0.01). Histomorphometric studies of reproductive organs could contribute to better develop the reproductive potential in this species. It is therefore recommended that season should be given urgent attention in any bull management system employed in Algeria in order to obtain the best semen quality.